Sex differences in strength at the shoulder: a systematic review - Tamar D. Kritzer; Cameron J. Lang; Michael W. R. Holmes; Alan C. Cudlip (PeerJ, 2024)
Background Understanding differential strength capability between sexes is critical in ergonomics and task design. Variations in study designs and outcome measures generates challenges in establishing workplace guidelines for strength requirements to minimize upper extremity risk for workers. The purpose of this systematic review was to collate and summarize sex differences in strength at the shoulder across movement directions and contraction types. Methods A total of 3,294 articles were screened from four databases (Embase, Medline, SCOPUS, and Web of Science). Eligibility criteria included observational studies, direct measurement of muscular joint, and healthy adult participants (18–65 years old). Strength outcome measures were normalized to percentages of male outputs to allow comparisons across articles. Results A total of 63 studies were included within the final review. Majority of articles observed increased strength in males; the gap between male–female strength was greater in flexion and internal/external rotation, with females generating ~30% of male strength; scaption strength ratios were most consistent of the movement groups, with females generating 55–62% of male strength. Conclusion Sex strength differences should be considered as an important factor for workplace task design as women are more at risk for occupational-related injuries than men in equivalent strength requirements. Differences in strength were not synonymous across motions; females demonstrated increased disparity relative to male strength in horizontal flexion/extension, forward flexion and internal/external rotation. Some movements had an extremely limited pool of available studies for examination which identified critical research gaps within the literature. Collating and quantifying strength differences is critical for effective workstation design with a range of users to mitigate potential overexertion risk and musculoskeletal injury.